The complete mitochondrial genome of Isochrysis galbana harbors a unique repeat structure and a specific trans-spliced cox1 gene - Fang, Jingping; Xu, Xiuming; Chen, Qinchang; Lin, Aiting; Lin, Shaoqing; Lei, Wen; Zhong, Cairong; Huang, Yongji; He, Yongjin (Frontiers in Microbiology, 2022)
The haptophyte Isochrysis galbana is considered as a promising source for food supplements due to its rich fucoxanthin and polyunsaturated fatty acids content. Here, the I. galbana mitochondrial genome (mitogenome) was sequenced using a combination of Illumina and PacBio sequencing platforms. This 39,258 bp circular mitogenome has a total of 46 genes, including 20 protein-coding genes, 24 tRNA genes and two rRNA genes. A large block of repeats ( 12.7 kb) was segregated in one region of the mitogenome, accounting for almost one third of the total size. A trans-spliced gene cox1 was first identified in I. galbana mitogenome and was verified by RNA-seq and DNA-seq data. The massive expansion of tandem repeat size and cis- to trans-splicing shift could be explained by the high mitogenome rearrangement rates in haptophytes. Strict SNP calling based on deep transcriptome sequencing data suggested the lack of RNA editing in both organelles in this species, consistent with previous studies in other algal lineages. To gain insight into haptophyte mitogenome evolution, a comparative analysis of mitogenomes within haptophytes and among eight main algal lineages was performed. A core gene set of 15 energy and metabolism genes is present in haptophyte mitogenomes, consisting of 1 cob, 3 cox, 7 nad, 2 atp and 2 ribosomal genes. Gene content and order was poorly conserved in this lineage. Haptophyte mitogenomes have lost many functional genes found in many other eukaryotes including rps/rpl, sdh, tat, secY genes, which make it contain the smallest gene set among all algal taxa. All these implied the rapid-evolving and more recently evolved mitogenomes of haptophytes compared to other algal lineages. The phylogenetic tree constructed by cox1 genes of 204 algal mitogenomes yielded well-resolved internal relationships, providing new evidence for red-lineages that contained plastids of red algal secondary endosymbiotic origin. This newly assembled mitogenome will add to our knowledge of general trends in algal mitogenome evolution within haptophytes and among different algal taxa.